MENANAMKAN KESADARAN MENJAGA KEAMANAN AKUN MENGGUNAKAN APLIKASI MCAFEE PADA SMPN 250 JAKARTA - Adella Aurelia Aryani; Aurelia Putri Dyfa Khan; Nadine Faiza Safiyana; Reivan Jovenko; Ahmad Khoiril Anam; Prima Dwi Yuliani; Hermina Manihuruk; Ilona Vicenovi Oisina S; Putri Utami Ramadhan; Lutfi Hardiyanto; Triadi, Edi Priyono; Sunardin, Sunardin; Sunardin, Muhamad Parhan (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
The increasingly widespread use of digital technology has brought new challenges in maintaining account security, especially among users who still have minimal understanding of various cyber threats. For this reason, we carry out Community Service Activities (PKM) at SMPN 250 Jakarta which aims to increase students' awareness of the importance of digital account security through education using the McAfee antivirus application. The methods used include interactive education about cyber threats such as malware and phishing, as well as tutorials on using the McAfee application to prevent cyber attacks. The activity begins with a pre-test to measure students' initial understanding and ends with a post-test as an evaluation of increased understanding. The results show an increase in students' knowledge of digital security, from a pre-test score of 58,97% to 92.76% in the post-test, which indicates the effectiveness of the education method. This increase shows the importance of digital account security education in the digital era, especially for technology users who are new to the internet. It is hoped that this activity can continue to be expanded to various groups to build awareness of the importance of maintaining the security of personal data from cyber threats. From this activity, we have produced several output products in the form of articles, posters, and videos. The article contains in-depth information related to the topic discussed, while the poster is designed to provide education in a visual and attractive manner. In addition, the video produced aims to provide interactive guidance and increase audience understanding of the material presented.